Effectiveness of the association of 2 probiotic strains formulated in a slow release vaginal product, in women affected by vulvovaginal candidiasis: a pilot study - Vicariotto, Franco; Del Piano, Mario; Mogna, Luca; Mogna, Giovanni (Journal of clinical gastroenterology, 2012)
Vulvovaginal candidiasis (VVC) is the second most common cause of vaginitis after bacterial vaginosis, and it is diagnosed in up to 40% of women with vaginal complaints in the primary care setting. Among Candida spp., Candida albicans is the most common infectious agent. The treatment of choice for uncomplicated VVC is achieved with single-dose or short-course therapy in over 90% of cases. Several topical and oral drugs are available, without evidence for superiority of any agent or route of administration. In any case, most classic treatments are unable to significantly offer a protection against possible recurrences. In recent years, probiotics are emerging as a new strategy to counteract VVC. In fact, they are well known for their ability to lower intravaginal pH, thus establishing a barrier effect against many types of yeasts. Some strains are also able to exert additional and more focused antagonistic activities mediated by specific molecules such as hydrogen peroxide and bacteriocins. For example, Lactobacillus fermentum LF5 (CNCM I-789) was successfully tested in 4 human trials involving a total of 340 women reporting VVC at enrollment. In any case, the way used to deliver probiotics to the vaginal environment represents a crucial point. The aim of this work was to first select 1 or more probiotic strains in vitro with an antagonistic activity on Candida yeasts and then to perform an in vivo human pilot study using an association of the most promising and active bacteria. For this purpose, 2 probiotic strains Probiotical S.p.A (Italy) were selected based on their strong in vitro inhibition activity toward 4 particular Candida species, namely C. albicans, Candida glabrata, Candida parapsilosis, and Candida krusei and subsequently tested in a human intervention pilot trial involving 30 women with VVC. The probiotics used, L. fermentum LF10 (DSM 19187) and Lactobacillus acidophilus LA02 (DSM 21717), were administered by means of slow release effervescent vaginal tablets (ActiCand 30 product). The main endpoint was the assessment of the establishment and maintenance of a barrier effect against Candida yeasts in women suffering from VVC. Thirty female subjects who were diagnosed with VVC by both microscopic examination and yeast culture were enrolled in the study and directed to apply a vaginal tablet once a day for 7 consecutive nights, followed by 1 tablet every 3 nights for a further 3-week application (acute phase) and, finally, 1 tablet per week to maintain a long-term vaginal colonization against possible recurrences. A medical examination of each patient was performed at enrollment (d₀), at the end of the first 4 weeks of treatment (d₂₈), and at the end of the second month of relapse prevention (d₅₆). The visual and microscopic examination was always accompanied by microbiological analyses of vaginal swabs to assess the presence of Candida. A statistical comparison was made between d₂₈, or d₅₆, and d0, and between d₅₆ and d₂₈ to quantify the efficacy against possible recurrences. The administration of the product ActiCand 30 was able to significantly solve Candida yeast symptoms after 28 days in 26 patients out of 30 (corresponding to 86.6%, P<0.001). At the end of the second month, recurrences were recorded, albeit not particularly serious, in only 3 out of 26 patients (11.5%, P=0.083) who were found to have fully healed at the end of the first month of treatment. This is a further confirmation of the long-term barrier effect exerted by the product. VVC has a very high incidence as 70% to 75% of women report at least 1 episode during the life. Many treatments are currently available but, despite a relatively high effectiveness in the relief of symptoms typically associated with acute infections, they are generally unable to offer a long-term protective barrier against possible recurrences. This study demonstrated the ability of ActiCand 30 to not only solve Candida infections in a very high percentage of women, but also to exert a long-term physiological defense due to the colonization of vaginal microbiota and adhesion of the mucosa to the epithelial cells. The special formulation of ActiCand 30, consisting of slow release effervescent vaginal tablets, is able to mediate 2 types of barrier effects, the first represented by the formation of an anaerobic environment due to the release of CO₂ and the second guaranteed by the colonization and adhesion to the vaginal epithelium of the 2 probiotics L. fermentum LF10 and L. acidophilus LA02.